2016
DOI: 10.5194/acp-16-1619-2016
|View full text |Cite
|
Sign up to set email alerts
|

OH reactivity and concentrations of biogenic volatile organic compounds in a Mediterranean forest of downy oak trees

Abstract: Abstract. Total OH reactivity, defined as the total loss frequency of the hydroxyl radical in the atmosphere, has proved to be an excellent tool to identify the total loading of reactive species in ambient air. High levels of unknown reactivity were found in several forests worldwide and were often higher than at urban sites.Our study presents atmospheric mixing ratios of biogenic compounds and total OH reactivity measured during late spring 2014 at the forest of downy oak trees of the Observatoire de Haute Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 68 publications
4
39
0
2
Order By: Relevance
“…Specifically, the correction for the deviation from the pseudo first-order conditions was determined from laboratory and field tests using certified concentration of gas standards containing propane and isoprene. The same procedure was applied in a previous field campaign in an isoprene-dominated environment (Zannoni et al, 2016). Previous field deployments of the same instrument were conducted in environments with low NO x concentrations, for which a correction for OH recycling by NO was not needed.…”
Section: Lsce Crm Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the correction for the deviation from the pseudo first-order conditions was determined from laboratory and field tests using certified concentration of gas standards containing propane and isoprene. The same procedure was applied in a previous field campaign in an isoprene-dominated environment (Zannoni et al, 2016). Previous field deployments of the same instrument were conducted in environments with low NO x concentrations, for which a correction for OH recycling by NO was not needed.…”
Section: Lsce Crm Instrumentmentioning
confidence: 99%
“…However, the agreement between measured and calculated reactivity is also a valuable result, because it indicates that all trace gases that are relevant for the photochemistry were measured. This was the case in environments that were influenced by anthropogenic OH reactants as in New York and in the North China Plain (Fuchs et al, 2016), in isoprene-dominated environments during daytime in a Mediterranean forest (Zannoni et al, 2016) and in a chamber study (Nölscher et al, 2014). In addition, the gap between measured and calculated OH reactivity could be closed in some field studies if oxygenated VOCs (volatile organic compounds) derived from model calculation were additionally taken into account (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of airborne measurements of OH reactivity (OHR) provides a method to evaluate the total sink of OH across a range of altitudes and a variety of locations and chemical environments (Mao et al, 2009). Previous work compared surface observations of OHR at a single site to the sum of individually calculated OHR components from measurements (Di Carlo, 2004;Yoshino et al, 2006;Sinha et al, 2008Sinha et al, , 2010Mao et al, 2010;Dolgorouky et al, 2012;Hansen et al, 2014;Nakashima et al, 2014;Nölscher et al, 2012Nölscher et al, , 2016Ramasamy et al, 2016;Zannoni et al, 2016Zannoni et al, , 2017 or from simple models (Ren et 10 al., 2006;Lee et al, 2009;Lou et al, 2010;Mogensen et al, 2011;Mao et al, 2012;Edwards et al, 2013;Kaiser et al, 2016;Whalley et al, 2016). Ferracci et al (2018) explored the impact of missing OHR estimated from surface observations on modeled global OH levels.…”
Section: Introductionmentioning
confidence: 99%
“…The diurnal cycle of OH total reactivity with a maximum around midday in a biogenic environment is well documented in literature from observations of OH reactivity for a Mediterranean forest (Zannoni et al, 2016), for temperate forests (Sinha et al, 2008;Ramasamy et al, 2016) but also for tropical forests Williams et al, 2016). The values of OH reactivity in or outside thermals in the present study are the lower bound of measurements over forests and gathered in Yang et al (2016), between 1 and 76 s −1 .…”
mentioning
confidence: 49%
“…As an example, over a Mediterranean forest, Zannoni et al (2016) measured the OH reactivity, as well as the concentration 30 of biogenic compounds. They found that isoprene was the dominant sink for OH and contributes up to 74% of OH total reactivity during daytime due to its high reactivity towards OH and its high concentration over the forested area.…”
mentioning
confidence: 99%